Enhancing Democratic Integrity: The Crucial Role of Election Supervision in Barru's 2020 Regional Head Elections - Kurniadi, Kurniadi; Madani, Muhlis; Khaerah, Nur (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2023)
Elections typically include infractions, thus Bawaslu was created to regulate the process and make elections more democratic. Bawaslu oversees and reduces general election infractions. Supervision evaluates if an activity is being executed as planned. The supervision equivalent of Das Sollen (plans) must match Das Sein (reality). According to this survey, the Bawaslu of Barru Regency has performed oversight well. (1) Bawaslu observed the Barru Regency regional head election from candidate selection to voting at sub-district and polling stations. Inspection Bawaslu examined indicators till he found head election breaches. The Bawaslu guidance and direction indicators help candidates and voters determine the extent of violations in the regional head election. Indicators Following up on Barru district regional head election breaches, Bawaslu took disciplinary action. This study's corrective action indicator is the Bawaslu's review to reduce violations in the head of blood election next year. (2) The COVID-19 epidemic, human resource quality, regulations, and community engagement affect Bawaslu supervision in regional head elections.